1993
DOI: 10.1093/brain/116.6.1387
|View full text |Cite
|
Sign up to set email alerts
|

Both primary motor cortex and supplementary motor area play an important role in complex finger movement

Abstract: In order to clarify the roles played by the primary motor cortex and the supplementary motor area in the execution of complex sequential and simple repetitive finger movements, regional cerebral blood flow (rCBF) was measured with PET using 15O-labelled water in five normal subjects. The PET data of each individual subject co-registered to his own MRI, was analysed. Compared with the resting condition, the mean rCBF was markedly increased in the contralateral sensorimotor cortex (M1-S1) and moderately increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
184
1
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 478 publications
(217 citation statements)
references
References 15 publications
28
184
1
4
Order By: Relevance
“…PET studies have shown that MI is activated as much by whole hand movements as by the independent movement of the fingers [5]. Simultaneous movements of two fingers causes even less activation of MI than sequential movements of these fingers with the frequency of movements being kept constant [29]. Thus, to move or not to move individual digits of the hand may be mediated by excitatory MI-activity.…”
Section: Discussionmentioning
confidence: 99%
“…PET studies have shown that MI is activated as much by whole hand movements as by the independent movement of the fingers [5]. Simultaneous movements of two fingers causes even less activation of MI than sequential movements of these fingers with the frequency of movements being kept constant [29]. Thus, to move or not to move individual digits of the hand may be mediated by excitatory MI-activity.…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of BCI, we are interested in the brain signal associated with movement intention preceding movement. The intention to move is associated with at least two cortical activities over sensorimotor and supplementary motor cortices: the movement-related cortical potential, which occurs about −1.5 s before the movement (Shibasaki et al 1993); and event-related desynchronization (ERD) or power decrease in alpha and beta bands, which occurs as early as 2s before the movement (Toro et al 1994a). Furthermore, these activities are available even though no movement occurs (Castro et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a great deal of interest in factors thought to affect the functional activation associated with movements of the hand and arm, such as the spatial and temporal complexity (Roland et al, 1980b;Colebatch et al, 1991;Grafton et al, 1992;Matelli et al, 1993;Kawashima et al, 1994a,b;Shibasaki et al, 1993;Sadato et al, 1996), whether movements were stimulus triggered or internally generated (Roland et al, 1980a;Fox et al, 1985;Deiber et al, 1991Deiber et al, , 1996Rao et al, 1993Rao et al, , 1997Boecker et al, 1994;Larsson et al, 1996), and the learning and acquisition of motor skills (Seitz et al, 1990Seitz and Roland, 1992;Jenkins et al, 1994;Schlaug et al, 1994;Grafton et al, 1995;Deiber et al, 1997;Hazeltine et al, 1997;Jueptner et al, 1997a,b;Shadmehr and Holcomb, 1997). However, to our knowledge there have not been any functional imaging studies which have specifically addressed the issue of the predictability of a motor response.…”
Section: Introductionmentioning
confidence: 99%